Nature, science and new types of scientific rationality in the works of W. Heisenberg - Karako, Petr S. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article is devoted to the analysis of the representations of prominent physicist of XX century W. Heisenberg about the nature, the character of human relations to it. It is emphasized his contribution to the development of quantum mechanics and new strategies of nature comprehension and their philosophical foundations. Particular attention is drawn to the disclosure of Heisenberg’s role in the justification of non-classical and post non-classical forms of scientific rationality. It is noted the importance of natural history ideas of this physics to the development of modern concept of philosophy of nature.